INTEGRASI FONOLOGI BAHASA MINANGKABAU DALAM BAHASA MELAYU BENGKULU - NFN Syamsurizal (tuahtalino, 2019)
This paper aims to describe the integration of the phonology of the Minangkabau language in the Bengkulu Malay language in sociolinguistic perceptions. The method used in this research is descriptive method. Data were collected using the listening method, with the basic techniques in the form of tapping techniques, free engages involved in competent listening and note taking techniques. The listening is done by tapping into the use of language in the "Belungguk Baso Bengkulu Community". Based on the results of data analysis, the integration of the Minangkabau language in Bengkulu Malay includes phonological aspects. Phonological integration can take the form of phonemes (at the beginning, middle and end), for example [acok] [cok] 'often' [antok] [ntok] 'silent' [jagok] [jgok] 'smart' [ateh] [ateh] 'on'; phoneme additions, for example [angik] [anggit] ‘musty smell’ [mada] [madal] ‘stubborn’; or through the process of changing phonemes ie / a / to / e /, for example [mancalik] [mencelik] 'seeing', [marapek] [merapek] 'docked', / u / being / o /, for example [urang gaek] [orang gaek] 'old man', / u / be / e /, for example [gulamo] [gelamo] 'fish name', / ui? / become / ut /, for example [kambuik] [kambut] 'pandan woven bag’.